LANGUAGE LEARNING STRATEGIES - Arif Ma'mun Rifa'i (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2018)
AbstractThis paper explains the important of learning, strategies and has finally discussed about characteristic of language learning strategies. The success of studying language is determined by how the learning and strategies are adopted. Learning is the process of interaction between students, teacher and material. Learning is also as assistance provided and designed by educators that involve the strategies in order that the process of acquiring knowledge and knowledge is achieved, mastery of skills and character can occur, and the formation of attitudes and trust in students are obtained. While strategic learning refers to the learner’s active such as negotiated interaction in target language in such communicative activities as clarification, confirmation, comprehension checks, requests, and etc. Strategic learning also refers to learners’ intentional engagement in the learning process by selectively attending to a learning problem, mobilization of the resources, deciding on the best available plan for action.Key words : learning, strategies, and language learning strategies.